The Factors Affecting Efficiency of Palm Kernel in Indonesia Palm Oil Industry - Yuli Eni, Christy Agustina, Metta Merlinna, Risya Bella, Lim Sanny (International Journal of Advanced Science and Technology, 2020)
The purpose of this study is to determine the factors affecting efficiency of palm kernel (PK) in Indonesia by using linear regression analysis method, which is simple regression analysis to determine the results of T-partial and multiple regression analysis to determine the results of F-simultaneous. There are six inputs, namely total concession, authorized capital, issued capital, paid up capital, total investment, and total employees as independent variables and one output, namely palm kernel (PK) as the dependent variable. The results of this study indicate that partially, the independent variables that have an effect on the Palm Kernel (PK) are total concessions (6.185017), total investment (5.309993), and total employees (4.854039) by comparing the T-Table value of 1.65 and the alpha value of 0.05 while simultaneously the results show that all independent variables have a significant effect on the Palm Kernel (PK) with an F-Statistic value of 11,61735, an F-table value of 1.94 and an alpha value of 0.05. Therefore, it is necessary to make the right decision to use the total concession, total investment, and total employees so that they can produce the maximum amount of Palm Kernel (PK) production.